An Assessment of the Influence of the Number of Micro-Enterprises on the Unemployment Rate in Poland with the Use of Panel Models - Huterska, Agnieszka; Zdunek-Rosa, Ewa (Olsztyn Economic Journal, 2017)
Small and medium-sized enterprises, in particular, micro-enterprises play an important role in generating gross value added as well as in job creation. The objective of the study is to evaluate the dependence between the number of micro-enterprises and the rate of unemployment in particular provinces in Poland in the years 2004–2014. The paper includes an analysis of cross-sectional and time series data using panel models. The conducted analysis showed that, as expected, a negative relationship exists between the number of micro-enterprises and the unemployment rate.